Pituitary Adenylate Cyclase Activating Polypeptide Anti-Mitogenic Signaling in Cerebral Cortical Progenitors Is Regulated by p57(Kip2)-Dependent CDK2 Activity - Carey, Rebecca G. (J Neurosci, 2002)
Generation of distinct cell types and numbers in developing cerebral cortex is subject to regulation by extracellular factors that positively or negatively control precursor proliferation. Although signals stimulating proliferation are well described, factors halting cell cycle progression are less well defined. At the molecular level, production and association of cyclins, cyclin-dependent kinases (CDKs), and CDK inhibitors (CKIs) regulate cycle progression. We now report that the endogenous peptide, pituitary adenylate cyclase activating polypeptide (PACAP), negatively regulates the cell cycle by inhibiting p57(Kip2)-dependent CDK2 activity in embryonic cortex. Protein levels of CDK2 and members of the CIP/KIP family of CKIs (p27(Kip1), p57(Kip2)) were detected in developing rat cortex from embryonic day 13.5 through postnatal day 2. With advancing development, CDK2 protein levels decreased, whereas CKI expression increased, suggesting that stimulatory and inhibitory cycle proteins control cell cycle exit. Using a well defined, nonsynchronized, 8 hr precursor culture, PACAP decreased the fraction of cells crossing the G(1)/S boundary, inhibiting DNA synthesis by 35%. CDK2 kinase activity was inhibited 75% by PACAP, whereas kinase protein and its regulatory cyclin E subunit were unaffected. Moreover, decreased kinase activity was accompanied by a twofold increase in levels of p57(Kip2) protein, but not p21(Cip1)or p27(Kip1), suggesting that p57(Kip2) mediates PACAP anti-mitogenic effects. Indeed, immunoprecipitation of CDK2 complex revealed increased p57(Kip2) association with the kinase and concomitant reduction in free inhibitor after PACAP exposure, suggesting that p57(Kip2) interactions directly regulate CDK2 activity. These observations establish a mechanism whereby anti-mitogenic signals actively induce cell cycle withdrawal in developing cortex.